The Meaning of Love for Students from Broken Homes - Puspita, Rizka Dwi; Adam; Abdul Manab (Nosipakabelo: Jurnal Bimbingan dan Konseling Islam, 2025)
This study aims to analyze the meaning of love for students from broken homes by examining how their parents' divorce experiences influence their views, attitudes, and behaviors toward love. This study applies a qualitative method using descriptive research, with the aim of systematically and accurately investigating circumstances, facts, events, conditions, and specific matters, and is designed to describe the perspectives of students from broken homes at the Faculty of Ushuluddin Adab and Dakwah (FUAD) at the State Islamic University (UIN) Datokarama Palu. Data was collected through in-depth interviews and observations, then analyzed descriptively to find patterns and meanings contained in the subjects' experiences. The results of the study show that students from broken homes tend to experience emotional gaps in interpreting love, where most view love with doubt, fear of loss, and difficulty in building trust, although there are also those who use this experience as motivation to build a healthier and more responsible love. In conclusion, the experience of a broken home shapes a complex, ambivalent, and dynamic understanding of love, which ultimately influences how students navigate interpersonal relationships and plan their future family life.